Pola dan Strategi Akulturasi Masyarakat Islam-Jawa dengan Hindu-Bali di Desa Pegayaman Bali Utara - I Nengah Punia; Wahyu Budi Nugroho (Universitas Udayana, 2022)
This study aims to examine the patterns and acculturation strategies of Javanese-Islamic society to Hindu-Balinese in Pegayaman Village, Buleleng, North Bali. The history of the existence of this society in Pegayaman Village has been going on since the 16th century and continues to live side by side in harmony with the Hindu-Balinese society until now. The research method used in this study is a descriptive-explanative qualitative research method. The study found that the pattern and acculturation strategy of the Javanese-Islamic society in Pegayaman Village with the Balinese ethnic society is in the form of semi-assimilation and integration strategies. These pattern and acculturation strategies are manifested both in culture as a system of ideas, patterned activities, and artifacts or objects made by humans. This article is expected to provide recommendations for acculturation patterns and strategies for society in various regions considering the plural and multicultural condition of the Indonesians.